Role for the Ventral Posterior Medial/Posterior Lateral Thalamus and Anterior Cingulate Cortex in Affective/Motivation Pain Induced by Varicella Zoster Virus - Kramer, Phillip R.; Strand, Jennifer; Stinson, Crystal; Bellinger, Larry L.; Kinchington, Paul R.; Yee, Michael B.; Umorin, Mikhail; Peng, Yuan B. (Frontiers in Integrative Neuroscience, 2017)
Abstract Varicella zoster virus (VZV) infects the face and can result in chronic, debilitating pain. The mechanism for this pain is unknown and current treatment is often not effective, thus investigations into the pain pathway become vital. Pain itself is multidimensional, consisting of sensory and affective experiences. One of the primary brain substrates for transmitting sensory signals in the face is the ventral posterior medial/posterior lateral thalamus (VPM/VPL). In addition, the anterior cingulate cortex (ACC) has been shown to be vital in the affective experience of pain, so investigating both of these areas in freely behaving animals was completed to address the role of the brain in VZV induced pain. Our lab has developed a place escape avoidance paradigm to measure VZV induced affective pain in the orofacial region of the rat. Using this assay as a measure of the affective pain experience a significant response was observed after VZV injection into the whisker pad and after VZV infusion into the trigeminal ganglion. Local field potentials (LFP) are the summed electrical current from a group of neurons. LFP in both the VPM/VPL and ACC was attenuated in VZV injected rats after inhibition of neuronal activity. This inhibition of VPM/VPL neurons was accomplished using a designer receptor activated by a designer drug (DREADD). Immunostaining showed that cells within the VPM/VPL expressed thalamic glutamatergic vesicle transporter-2, NeuN and DREADD suggesting inhibition occurred primarily in excitable neurons. From these results we conclude 1) that VZV associated pain does not involve a mechanism exclusive to the peripheral nerve terminals and 2) can be controlled, in part, by excitatory neurons within the VPM/VPL that potentially modulate the affective experience by altering activity in the ACC.